1135 Improving Surgical Discharge Summaries. (12th October 2021) - Oyewole, B; Liu, C; James, N; Sandhya, A; Ma, J; Jethwa, P
Abstract: Introduction: Discharge summaries are a means of communication to the patient, the GP and for medical records. An initial audit showed surgical discharge summaries contained misleading information and sometimes omitted relevant information. Changes were implemented to improve the accuracy of surgical discharge summaries. Method: The initial audit assessed the accuracy of discharge summaries over a two-week period and the re-audit was conducted after implementation of change over a similar time period. Data was extracted from electronic patient records (EPR). Change implementation included educating the surgical team on the need for accurate discharge summaries. The EPR team was notified of the intrinsic error in the PowerChart system which is widely used in various NHS Trust. Results: Incidence of misdiagnosis or misleading diagnosis in discharge summaries reduced from 42% to zero, lack of relevant investigations decreased from 7% to 1%, No follow up status reduced from 23% to 10% (usually post appendicectomy patients which are not routinely followed up but this needs to be stated in the discharge summary for clarity), at both initial audit and re-audit all patients had relevant surgery or procedures done included in their discharge summaries while the rate at which relevant medications were not stated in the discharge summary decreased from 4% to zero. Conclusions: Discharge summaries are vital for record keeping and are usually the only written information a patient receives regarding their hospital stay. It is important that errors in EPR systems be flagged up for review.